2019
DOI: 10.9734/ijpss/2019/v28i430117
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical Characterization of Blends Based on Milk and Catole Coconut Pulp

Abstract: Aims: Coconut catole is the fruit of the Syagrus cearenses palm tree, whose pulp is usually eaten in its natural form. The formulation of blends is intended to improve the acceptance of fruit with potential to be exploited. The objective of this work was to evaluate the physico-chemical characteristics of the whole coconut pulp and the blends formulated with the pulp and milk. Place and Duration of Study: The coconut catole (Syagrus cearensis) were collected in the surroundings of location 551'30 "S, 35º… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…For non-reducing sugars (NRS), guava reached the highest content again, while in pitanga, the value is not very expressive. Ribeiro et al [27], evaluating acerola pulp and acerola blended with seriguela, found in acerola RS levels of 6.00 g glucose/100 g, TS of 6.87 g glucose/100 g and NRS of 0.87 g sucrose/100 g, and in the prepared blend, RS of 6.3 g glucose/100 g, AT of 8.3 g glucose/100 g and NRS of 2.0 g sucrose/100 g. Matos et al [31], analyzing the same parameters, obtained results of 0.01 g glucose/100 g (RS), 3.26 g glucose/100 g (TS) and 3.08 g sucrose/100 g (NRS) for acerola pulp and 0.02 g glucose/100 g (RS), 5.30 g glucose/100 g (TS) and 5.02 g sucrose/100 g (NRS) for mixed pulp of acerola and jambolan.…”
Section: Physicochemical Characterizationmentioning
confidence: 94%
See 1 more Smart Citation
“…For non-reducing sugars (NRS), guava reached the highest content again, while in pitanga, the value is not very expressive. Ribeiro et al [27], evaluating acerola pulp and acerola blended with seriguela, found in acerola RS levels of 6.00 g glucose/100 g, TS of 6.87 g glucose/100 g and NRS of 0.87 g sucrose/100 g, and in the prepared blend, RS of 6.3 g glucose/100 g, AT of 8.3 g glucose/100 g and NRS of 2.0 g sucrose/100 g. Matos et al [31], analyzing the same parameters, obtained results of 0.01 g glucose/100 g (RS), 3.26 g glucose/100 g (TS) and 3.08 g sucrose/100 g (NRS) for acerola pulp and 0.02 g glucose/100 g (RS), 5.30 g glucose/100 g (TS) and 5.02 g sucrose/100 g (NRS) for mixed pulp of acerola and jambolan.…”
Section: Physicochemical Characterizationmentioning
confidence: 94%
“…In total flavonoids (TF), all samples differed statistically from each other (p < 0.05), with acerola showing the highest content (12.64 mg/100 g), followed by the blend (8.22 mg/100 g), favored by the high content provided by acerola, presenting twice the value determined in pitanga (4.05 mg/100 g) and approximately four times that of guava (1.91 mg/100 g). Higher levels of TF were quantified by Silva et al [39] in samples of pitanga in natura with a value of 28.7 mg/100 g, in frozen pitanga pulp with a value of 28.0 mg/100 g, and in pitanga jelly with a value of 35.7 mg/100 g; by Omayio et al [42], who reported values ranging from 188.25 to 250.66 mg/100 g for three different varieties of guavas produced in Kenya; and by Matos et al [31], who determined a value of 16.16 mg/100 g in acerola pulp. Flavonoids are antioxidants and have antimutagenic, anti-inflammatory, antidiabetic, antimicrobial and antiviral effects [44].…”
Section: Bioactive Compoundsmentioning
confidence: 95%